Silicone auricular prosthetics with adhesive retention: a case report - Nasruddin; Rustan Ambo Asse; Eri Hendra Jubhari (Indonesian Journal of Prosthodontic, 2022)
A-18-years-old male came to the Dental and Oral Hospital of Hasanuddin University with a complaint of losing his left ear due to a traffic accident several years ago and often feeling pain in his ear especially when blown by strong winds. The patient wants to make an auricular prosthesis so that his self-esteem returns to normal. The extraoral exa-mination showed convex profile, oval-shaped face, symmetrical eyes, nose and lips, submandibular lymph nodes ex-hibit without complaints. The right and left ears are not symmetrical. Manufacture of silicone auricular prosthesis with adhesive retention. Anatomical impressions of the patient's and his siblings' ears were performed as a guide for duplication of the patient's left ear using an irreversible hydrocolloid impression material. The wax pattern of the ear prosthesis that had been made on the die was paired with the patient to check the size accuracy and left and right symmetry. Then proceed with the process of acrylic packing and coloring. After the laboratory process was com-pleted, insertion is carried out. Signs of successful treatment: silicone ear prosthesis with adhesive retention has restored the patient appearance and self-esteem.